Role of C-reactive protein in acute pancreatitis: an observational study in a tertiary care centre - Dogra, Varun; Peer, Javid Ahmad; Gilkar, Ishfaq Ahmed; Mushtaq, Umer (International Surgery Journal, 2022)
Background: Acute pancreatitis is significant reason for intense abdominal torment. The job of diagnostic markers (pancreatic enzymes like amylase and lipase) as prognostic pointers has been a disappointment. C-reactive protein (CRP) assessment is modest and effective option. In this concentrate we have endeavored to check whether a solitary and early assessment of CRP levels is a viable indicator of morbidity and mortality in acute pancreatitis. Methods: This was a prospective observational study done at Government Medical College Srinagar Kashmir for a period of three years from May 2015 to April 2018. Fifty patients diagnosed to have acute pancreatitis were included in this study. Their CRP levels were sent on second day of admission and computed tomography (CT) scan done after 72 hours of admission. Demographic variables were recorded along with local and systemic complications and compared with CRP levels. Results: In this study of 50 patients, we found that most of the patients of pancreatitis were young to middle aged males, a majority of whom belonged to fourth decade of life. We found that levels of CRP rise as age and severity progresses. CRP levels also remains on higher side in various local complications like necrosis, acute fluid collection etc., however a statistical significance could not be ascertained. Conclusions: Acute Pancreatitis is a life-threatening disease with a wide spectrum of clinical symptoms. C Reactive Protein as a prognostic marker has shown promising results in earlier studies. There is an need to further study its role so as to reduce the mortality and morbidity associated with acute pancreatitis.